A SURVEY OF UNDERGRADUATE TEACHING OF CLINICAL NEUROLOGY IN THE UNITED KINGDOM 2012. Issue 11 (9th October 2013) - Sharma, Kanchan; Athauda, Dilan; Robbins, Emily
Abstract : Background: Neurology has historically been a subject of great difficultly and fear for undergraduate medical students, despite it accounting for a significant proportion of hospital medical admissions. 1 The lack of adequate teaching can lead to "neurophobia" defined in 1994 as "a fear of the neural sciences and clinical neurology" by medical students and doctors. 2 3 Whilst this does not have a DSM–IV classification one can appreciate the nervous system is the most complex organ in the body and hence a complicated and difficult subject to learn. Teaching this subject to undergraduate MB ChB students has been especially challenging; students seemed ill equipped with a vital understanding of how empirical neuroscientific principles integrate with pathology which can then be applied to patients with clinical problems. This was compounded by students rotating to another speciality too soon, without enough time to build on their knowledge and skills adequately. They learn enough to be competent but not enough to be proficient. They know how to perform a neurological exam but do not know how to interpret the signs. Previous surveys published over 20 years ago show great disparity in the course duration and content of neuroscience attachments, I therefore decided to investigate if this pattern still persisted. 4 Methodology: Undergraduate neurology course leads were identified for all 30 clinical medical schools in the UK. They were emailed an online questionnaire survey and non–respondents were followed with a hard copy. The questionnaire focused on eliciting course duration, timing within the clinical programme, course infrastructure, teaching methods employed and acknowledgment of funding. Results: Results of the national survey revealed a surprisingly wide discrepancy in course programme structure and duration, sometimes even within the same medical school. Course duration varied from one week full time to twelve weeks part time. Thirty percent of respondents did not guarantee undergraduate neurology being taught by a neurologist. Discussion: Medical schools are independent institutions with the right to configure clinical training as they see fit provided they produce doctors who meet the standards required for pre–registration. It is therefore surprising that such a large discrepancy exists for curriculum provision between medical schools. Through collaboration neuroscience educators should work synergistically to create a national pool of teaching materials, thereby reducing duplication of work and improving the quality of learning resources for all undergraduate neurology students.